Observance of Principles of Mutual Consideration (PMC) and Its Relation to the Presence of Three Levels of Politeness - Apriani Mulyawati (Passage, 2013)
The study entitled “Observance of PMC and Its Relation to the Presence of Three Levels of Politeness” investigates politeness realizations according to Principles of Mutual Consideration (PMC) between two different cultures and its relation to the presence of three levels of politeness: pre-event, on-the-spot, and post-event politeness as proposed by Aziz (2000). PMC works as a cause and effect logic wgich consists of four sub-principles: i.e. harm and favor potential, shared-feeling, prima-facie, and continuity principles. The main data of the study were retrieved from www.rcti.tv on 26th April, 2010 which contained the opening-part of an interview script between an Indonesian Journalist and the President of the Unites States. Using the PMC framework, the study found that there is balanced-order in observing PMC’s sub-principles. This is due to the fact that both the interviewer and the interviewee had the intention to favour one another. This was realized in their complete observance of four PMC’s sub-principles. The study concluded that the observance of PMC together with its three levels of politeness is mainly motivated to balance and create harmony.Keywords: Principle of Mutual Consideration (PMC), Three Levels of Politeness